Elephants, Ivory, and Charcoal: An Ecological Perspective - Miller, Robert D. 1966-2023 (1986)
Using ecological data on elephant diet and habitat can shed some light on the appearance of elephant herds in north Syria during the late second and early first millennia B. C. A period of reduced human settlement density allowed the growth of secondary forest, which provided the woody material essential to elephant diet. With the increasing demand for charcoal and fuel among sedentary communities in the Iron Age, forest resources declined to the point where elephant populations became extinct. Changes in metallurgy, politics, and patterns of rangeland management may also have contributed to the reduction of elephant populations to the point where they became vulnerable to overhunting.